Anxiety and Depression as Predictors of Quality of Life in Cardiovascular Patients - Fouzia Naeem Effendi; Anusha Khattak; Maryam Khan; Sania Nisar; Kashaf Fatima; Eman Tariq (ziauddin University, 2024)
Background: Research indicates that patients with cardiovascular diseases (CVDs) often experience considerable anxiety, depression, or both following an initial cardiovascular event and tend to experience poorer quality of life (QOL). Thus, this study aimed to investigate if anxiety and depression can serve as predictors of QOL in cardiovascular patients. Methods: An online cross-sectional survey was conducted from February to September 2022 and included only Karachi residents. Participants were included by non-probability convenience sampling. The Diagnostic and Statistical Manual IV Hospital Anxiety and Depression Scale (DSM-IV HADS) and the WHO Quality of Life Brief (WHOQOL-BREF) questionnaire were self-administered. A total of 400 responses were obtained, of which only 369 fulfilled the inclusion criteria, i.e. patients diagnosed with CVD by a cardiologist, aged ≥18, and those who could communicate in English or Urdu. Descriptive frequencies and multiple regression analyses were performed using multiple regression using SPSS v.25. Results: Most participants were male with a mean age of 51.6±12.4 years and an average time of 3.82±4.86 years since they were diagnosed. Multiple regression analyses showed that anxiety and depression were significant predictors (p<0.001) for decreased quality of life. There was a moderate correlation in the physical, social, and environmental domains (r = 0.637, 0.651, and 0.635) and a weak association in the social domain with an R-value of 0.483. Conclusion: The findings suggest that addressing anxiety and depression in patients can significantly enhance their lifespan by improving their QOL. Addressing these concerns could lead to a more comprehensive approach to patient care. Keywords: Anxiety, Depression, Cardiovascular Diseases, Quality of Life.